Sustainability of mural art trend in the urban environment: a review on literature / Muhammad Falihin Jasmi ... [et al.] - Jasmi, Muhammad Falihin; Abdul Ghani, Izham; Abdullah, Marina; Bahaluddin, Azrul (2021)
This paper presents a review on the sustainability of the mural art trend as one of the approaches of public art integration in the urban environment. The methodology engaged for this paper is primarily through a comprehensive analysis of secondary data from scholarly articles, journals and academic publications. This study examines the pertaining issues that occurred from the current inclination of mural art as a part of the city's identity enhancement, which is then directed to the sustainability of the art pieces throughout the ages. This paper underlines the challenges and determination in sustaining mural art and concludes that the awareness, acceptance and effort from all relevant parties are crucial for this cause.